Identifikasi Sumber Glutamat Bebas pada Menu Hidangan Indonesia - Nuri Andarwulan; Lilis Nuraida; Purwiyatno Hariyadi; Siti Madanijah; Zulaikhah Zulaikhah; Desty Gitapratiwi (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2015)
The study aimed to evaluate free glutamate content occurs naturally in prepared foods or dish menus. Fifteen selected Indonesian dish menus were categorized to three major groups, i.e. dish menu with monosodium glutamate (MSG) addition, dish menu with seasoning and/or condiment containing glutamate addition, and dish menu with MSG, seasoning and/or condiment containing glutamate addition. Each dish menu was prepared at the kitchen laboratory by standardizing the ingredients, composition and cooking process, followed by analysis of free glutamate content in dish menu, its raw material mix, and basic seasoning using HPLC method. The study results showed that raw materials such as chicken, fermented-tofu solid waste (oncom), meatball, cabbage, fried onion, tomato, and fried potato contributed to the free glutamate content in dish menus. Addition of MSG, seasoning and/or condiments de nitely contributed to free glutamate content in the dish menus, ranged 9.8-142.9% for MSG added and 7.9- 100% for seasoning and/or condiments added. The dish menus with MSG addition which contributed to higher free glutamate content were fried tempe, rice cake with vegetable soup in coconut milk, and spiced chicken soup. Meanwhile, the dish menus with seasoning/ condiment addition contributed to higher free glutamate content were stir-fry water crest, mixed vegetable in chicken soup, chicken rice porridge. Cooking practices could increase or reduce free glutamate content in dish menus, ranged from -86.2 to 43.3%.